Semiotic Analysis of Masculinity in High and Low the Movie 3 Final Mission: Janet Saltzman Chafetz Theory - Bililah, Dimas Fisal; Widodo, Wahyu Unggul; Sulistiyaningsih, Eka Fanti (English Education and Literature Journal (E-Jou), 2024)
This research intends to analyze and search for 7 areas of Chafetz's masculinity using Roland Barthes' semiotic method in the film High and Low the Movie 3 Final Mission. The semiotics presented by Barthes regarding the meaning of denotation and connotation were implemented in analyzing 12 screenshots of scenes presented in the film High and Low the Movie 3 Final Mission. Then the 12 research findings were analyzed using a predetermined method, namely using Janet Saltzman Chafetz's theory regarding 7 areas of masculinity. This study uses a qualitative method. Based on semiotic analysis in the film High and Low the Movie 3 Final Mission, it has a relationship with the 7 areas of masculinity proposed by Janet Saltzman Chafetz. Namely the character's physical condition and appearance that is fashionable, the figure of provider or breadwinner for both oneself and many people, aggressive nature and experience in fighting, the ability to regulate one's emotional condition, the ability to think rationally and based on logic/knowledge, high interpersonal attitude, and spirit and fair competitive attitude.